Proposed Marketing Strategy for Mr. Komot Café and Cakeshop - Lestari, Adinda Ayu; Wibowo, Satya Aditya (The Indonesian Journal of Business Administration, 2014)
Abstract. As the culinary city within Indonesia, Bandung surely has a potential in culinary which can lead into a great opportunity for many business people within food business. Therefore, Mr.Komot café and cakeshop as one of café in bandung try to catch this opportunity within food business. Mr.Komot was established on October 3rd, 2010 and offers many delicious food and beverage, especially cakes. Even though Mr.Komot has been existed in food business within Bandung for more than three years, people seem to choose other café more than they choose to come to Mr.Komot. The business issues which are faced by Mr.Komot are sales performance and the lack of brand awareness of Mr.Komot. The internal analysis was conducted through STP and Marketing Mix analysis while the external analysis was conducted through Porter’s Five Analysis and competitor analysis. After conducting internal and external analysis then SWOT can be defined. As the result, the root cause of this research can be found and the next step to do is proposing the business solution. Survey was conducted through questionnaire to know about the importance and performance of Mr.Komot Marketing Mix from the respondents. There are five attributes of root cause which consist of Product, Price, People, Physical Evidence and Promotion which are divided into critical quadrant based on Importance-Performance Analysis (IPA). Keywords: food business, bandung, café, marketing strategy